FORTIFICATION OF CAKE WITH CHICKPEA FLOUR AS A PROTEIN ENHANCER - CHANDRASHREE LENKA*, TRIPTI KUMARI; TRUPTI PRADHAN (The Journal of Research ANGRAU, 2020)
The study was conducted (2018-19) to develop high protein low calorie cake with chickpea flour along with whole wheat flour and other ingredients in different proportions as a protein supplement to combat malnutrition. Four cakes were prepared including control (whole wheat flour only).Nutritional quality and the sensory evaluation of cake was done in accordance with Nutritive value of Indian foods ICMR, numerical scoring test and nine point hedonic scale for six sensory characteristics respectively. Cake C3 prepared with ratio of 4:1 chickpea flour and wheat flour was found to be best one with respect to its nutritive value and sensory characteristics.Significantly high difference at P<0.05 between the cakes in respect of colour, appearance, taste, overall acceptance & texture was observed. Cost of the developed cakes was found to be two to three folds cheaper in comparison to cakes available in the market. Thus, Cake 3 fortified with chickpea flour with less sugar and less oil containing 12% protein can be recommended as a high protein supplement food to reduce malnutrition among children and starvation among adults.